Analysis Of the influence of work life balance, leadership, religiosity and high performance work practices on employee performance mediated by employee engagement - Alden Nelson Nelson; Vinolia Angellius (Enrichment : Journal of Management, 2023)
This study to test and analyze can affect work life balance, leadership, religiosity, and high performance work practices to employee engagement. The population in this study are employees from logistics companies that focus on providing transportation services and the number of samples used 185 respondents. The research method used in this study is a quantitative method using smart PLS 3.0 for data processing. The results showed that leadership and religiosity had a significant positive effect on employee engagement, leadership style, work life balance, high performance work practices had a significant positive effect on employee performance. leadership and religiosity have a significant positive effect on employee performance which is mediated by employee engagement while high work performance and work life balance have no significant effect on employee performance which is mediated by employee engagement.